Inconsistency of Curriculum of Education in Indonesia - Wawan Kusnawan (ISTAWA, 2019)
The life of the nation has not shown maximum results. Therefore the generation that was produced experienced a decline in adab, morality, and nationalism. This causes much juvenile delinquency such as students against teachers, fights between students, free sex (free sex), drug use, etc. This shows that education in Indonesia is problematic. The solution, there must be an integrated system in the components contained in the teaching and learning process. This unified system includes an intra or extra curriculum, in this text will be discussed further and in detail.Kehidupan bangsa belum menunjukkan hasil yang maksimal. Karenanya generasi yang dihasilkan mengalami kemerosotan adab, moral dan nasionalisme. Hal tersebut menyebabkan banyaknya terjadi kenakalan remaja seperti murid melawan guru, perkelahian antar pelajar, pergaulan bebas (free sex), penggunaan narkoba, dsb. Ini menunjukan bahwa pendidikan di Indonesia bermasalah. Solusi, harus adanya sistem integrated dalam komponen-komponen yang termuat dalam proses belajar mengajar. Sistem integrated ini meliputi kurikulum intra ataupun ekstra, dalam naskah ini akan dibahas lebih lanjut dan detail.